2018
DOI: 10.12688/f1000research.14078.1
|View full text |Cite
|
Sign up to set email alerts
|

Early storybook reading and childhood development: A cross-sectional study in Iran

Abstract: Background : Development is a process that continues from childhood to death, and most developmental changes occur during childhood. UNICEF introduced early storybook-reading (ESR) and storytelling as part of child care indicators. The aim of this study was to investigate the status of book-reading to children and its relationship with early childhood development in Iran. Methods: This is a descriptive-analytic study conducted in Tehran April-May 2017. In total, 272 mothers of children aged 3-30 months, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
6
0
2
Order By: Relevance
“…When examining the relationship between infant cognitive development and SPPs, our study found that reading books and singing songs were highly correlated with infant cognitive outcomes, which suggests that these activities encourage high levels of caregiver-infant engagement. Multiple studies that examine the relationship between reading books and early cognitive development have found that reading books to young children fosters lifelong cognitive functions, regardless of family SES [ 36 , 37 , 38 ]. Similarly, studies that examine the relationship between singing songs to infants and cognitive outcomes have found that early exposure to singing is beneficial to general, lifelong cognitive outcomes [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…When examining the relationship between infant cognitive development and SPPs, our study found that reading books and singing songs were highly correlated with infant cognitive outcomes, which suggests that these activities encourage high levels of caregiver-infant engagement. Multiple studies that examine the relationship between reading books and early cognitive development have found that reading books to young children fosters lifelong cognitive functions, regardless of family SES [ 36 , 37 , 38 ]. Similarly, studies that examine the relationship between singing songs to infants and cognitive outcomes have found that early exposure to singing is beneficial to general, lifelong cognitive outcomes [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sénéchal et al (1998) reported that parents had 61 to 80 children's books in the home and Stephenson et al (2008) reported that parents had 100-199 books. On the other hand, among the parents in Tehran, Iran, Sajedi et al (2018) reported that the average number of children books was ten. Taken together, there may be sociocultural and/or environmental factors that impact the number of books in the home.…”
Section: Age and Frequency Of Exposurementioning
confidence: 99%
“…(28,31,41,42,(45)(46)(47)(48)(49)(50) Studies also suggest that literacy promotion interventions are effective in increasing shared reading behaviors, and that these positively impact child language and literacy outcomes regardless of sociocultural background. (19,48,(51)(52)(53)The promotion of shared reading offers a valuable opportunity to improve child health globally. (54) Although the families in our sample had a relatively higher level of education and higher rates of maternal employment than average for Jordan, this nding may be related to the demographic targeted; speci cally, parents of young children.…”
Section: Resultsmentioning
confidence: 99%